Inflammation Mediates the Development of Aggressive Breast Cancer Following Radiotherapy - Ma, Lin; Gonzalez-Junca, Alba; Zheng, Yufei; Ouyang, Haoxu; Illa-Bochaca, Irineu; Horst, Kathleen C.; Krings, Gregor; Wang, Yinghao; Fernandez-Garcia, Ignacio; Chou, William; Barcellos-Hoff, Mary Helen (Clinical cancer research, 2021)
Women treated with radiotherapy before 30 years of age have increased risk of developing breast cancer at an early age. Here, we sought to investigate mechanisms by which radiation promotes aggressive cancer. The tumor microenvironment (TME) of breast cancers arising in women treated with radiotherapy for Hodgkin lymphoma was compared with that of sporadic breast cancers. To investigate radiation effects on carcinogenesis, we analyzed tumors arising from -null mammary transplants after irradiation of the target epithelium or host using immunocompetent and incompetent mice, some of which were treated with aspirin. Compared with age-matched specimens of sporadic breast cancer, radiation-preceded breast cancers (RP-BC) were characterized by TME rich in TGFβ, cyclooxygenase 2, and myeloid cells, indicative of greater immunosuppression, even when matched for triple-negative status. The mechanism by which radiation impacts TME construction was investigated in carcinomas arising in mice bearing -null mammary transplants. Immunosuppressive TMEs (iTME) were recapitulated in mice irradiated before transplantation, which implicated systemic immune effects. In nu/nu mice lacking adaptive immunity irradiated before -null mammary transplantation, cancers also established an iTME, which pointed to a critical role for myeloid cells. Consistent with this, irradiated mammary glands contained more macrophages and human cells cocultured with polarized macrophages underwent dysplastic morphogenesis mediated by IFNγ. Treating mice with low-dose aspirin for 6 months postirradiation prevented establishment of an iTME and resulted in less aggressive tumors. These data show that radiation acts via nonmutational mechanisms to promote markedly immunosuppressive features of aggressive, RP-BCs.